2018
DOI: 10.1016/j.chembiol.2018.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for Inhibitor-Induced Hydrogen Peroxide Production by Kynurenine 3-Monooxygenase

Abstract: Kynurenine 3-monooxygenase (KMO) inhibitors have been developed for the treatment of neurodegenerative disorders. The mechanisms of flavin reduction and hydrogen peroxide production by KMO inhibitors are unknown. Herein, we report the structure of human KMO and crystal structures of Saccharomyces cerevisiae (sc) and Pseudomonas fluorescens (pf) KMO with Ro 61-8048. Proton transfer in the hydrogen bond network triggers flavin reduction in p-hydroxybenzoate hydroxylase, but the mechanism triggering flavin reduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 72 publications
0
34
0
Order By: Relevance
“…Furthermore, regions of positive electrostatic potential in the active site would situate the anionic reduced flavin to the "in" position adjacent to the substrate, in addition to previously promoting the formation of the substrate phenolate [70]. Interestingly, a hydrogen-bonding network is not found in the active site of kynurenine 3-monooxygenase (KMO), in which conformational changes and flavin reduction are triggered by π-π interactions between the substrate and the loop above the re-side of the isoalloxazine group [71].…”
Section: Comparison Of Nahg With Others Flavoprotein Monooxygenasesmentioning
confidence: 99%
“…Furthermore, regions of positive electrostatic potential in the active site would situate the anionic reduced flavin to the "in" position adjacent to the substrate, in addition to previously promoting the formation of the substrate phenolate [70]. Interestingly, a hydrogen-bonding network is not found in the active site of kynurenine 3-monooxygenase (KMO), in which conformational changes and flavin reduction are triggered by π-π interactions between the substrate and the loop above the re-side of the isoalloxazine group [71].…”
Section: Comparison Of Nahg With Others Flavoprotein Monooxygenasesmentioning
confidence: 99%
“…Studies on the structure and mechanism of KMO in animal (Zhang et al, ) have been discussed in the past (Kim et al, ; Smith et al, ). KMO is situated in the outer membrane of mitochondria (Quan et al, ) as a membrane‐associated protein (Gao et al, ), and its crystal structure was found by Amaral et al () as well as the first successful bacterial ( Escherichia coli ) expression of active human KMO enzyme expressed in the soluble fraction found by Wilson et al ().…”
Section: The Structure and Function Of Kmomentioning
confidence: 99%
“…The enzyme from P. fluorescens (PfKMO) is a soluble enzyme with 37% identity to human KMO that can be expressed heterologously in Escherichia coli (Crozier and Moran, 2007). The crystal structures of PfKMO with a number of inhibitors and L-kynurenine bound have been solved recently (Hutchinson et al, 2017; Gao et al, 2018; Kim et al, 2018). The structure of PfKMO (Figure 3) is very similar to that of ScKMO.…”
Section: The Three Dimensional Structure Of Kynurenine Monooxygenase mentioning
confidence: 99%
“…The first structure of hKMO was reported recently (Kim et al, 2018). The crystal structure was solved to a resolution of 2.1 Å after engineering the deletion mutant, hKMO-374 (residues 1-374), in which the transmembrane domains were deleted, in order to obtain a human KMO protein suitable for crystallization.…”
Section: The Three Dimensional Structure Of Kynurenine Monooxygenase mentioning
confidence: 99%
See 1 more Smart Citation